Exemption from liability under Article 79 of the United Nations Convention on Contracts for the International Sale of Goods: general characteristics and conditions of application - I.M. Horobets (Аналітично-порівняльне правознавство, 2024)
The article examines the issue of the exemption from liability under Article 79 of the United Nations Convention on Contracts for the International Sale of Goods. This provision is crucial in international trade, as it outlines conditions under which a party may be exempted from liability for nonperformance due to «impediments beyond his control». The study is particularly relevant in light of the 2022 Russian invasion of Ukraine, which disrupted many international contracts.